MICROFINANCING WOMEN: WHAT DOES IT MEAN FOR THEM? - Mita Yesyca (Sociae Polites, 2021)
Many development programs in poor countries are now targeting women so that they can participate actively and get the fruits of development for their own good, including the microfinance program. However, the meaning and significance of such an idea deserve more attention. To show the set of identities, social relations, political possibilities and the ethical outcomes of ‘microfinancing women,’ the expressions of such potent combination between women and microfinance in today’s practices, the values that justify the claims, and also whose culture or what ideology which appears in the justification or reasoning for the claims are investigated. The data showed that specific women are the “promising” target. Instead of empowering women for the sake of themselves, microfinance produces entrepreneurial subjects on them so that they can enter the global market. A critical examination of microfinancing women entails a reexamination of the discourse, its implications, and the fundamental problematic ideology behind the on-going trend. Keywords: Microfinance, women, text, entrepreneur, globalization